2012
DOI: 10.1161/strokeaha.112.656124
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Transverse Sinus Thrombosis From Congenitally Atretic Cerebral Transverse Sinus With CT

Abstract: Background Transverse sinus thrombosis can have nonspecific clinical and radiographic signs. We hypothesized that the novel “sigmoid notch sign” (on head CT) can help differentiate transverse sinus thrombosis from a congenitally atretic sinus among individuals with absent signal in one transverse sinus by magnetic resonance venography (MRV). Methods We retrospectively evaluated 53 subjects with a unilaterally absent transverse sinus signal on MRV. 11 had true transverse sinus thrombosis and 42 had an atretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
0
14
0
2
Order By: Relevance
“…Incidence was higher than others have found previously published. [1][2][3][4][5][7][8][9][10][11] Including the recent study of Coutinho et al, 1 that demonstrated an incidence of 13 million person-years, which was also substantially higher than expected from previous research. They studied a 3-year period in an organization with comparable access to neuroimaging; however, they identified cases solely using clinical coding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence was higher than others have found previously published. [1][2][3][4][5][7][8][9][10][11] Including the recent study of Coutinho et al, 1 that demonstrated an incidence of 13 million person-years, which was also substantially higher than expected from previous research. They studied a 3-year period in an organization with comparable access to neuroimaging; however, they identified cases solely using clinical coding.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The low incidence and incongruous presentation of CVT often lead to late diagnosis. [1][2][3][4][5][6][7][8]11 The incidence of CVT has been reported as being between 2 and 5 million per year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insbesondere muss z. B. eine Hypoplasie des Sinus transversus von einer Thrombose unterschieden werden [5]. Intrazerebrale Blutungen finden sich bei 30%-40 % aller Patienten, hingegen sind subdurale oder subarachnoidale Blutungen deutlich seltene [3].…”
Section: Introductionunclassified
“…The incidence of CVST is 2-5/10 000 000/year, accounting for 0.5%-1% of all stroke. [1][2][3][4][5][6][7][8][9] Recently, the incidence of CVST has been rising with the advent of diagnostic techniques. Two studies in Iran have reported CVST affects 12.3-13.49/10 000 000/year, 3 10 and another study in Saudi Arabia has shown that CVST affects 70/10 000 000/year.…”
mentioning
confidence: 99%